دراسة الكفاءة الاقتصادية لإنتاج أزهار الورد الجوري في الساحل السوري - عليو, محمود; الرفاعي, عبدالهادي; سرحيل, زياد (Latakia University Journal -Biological Sciences Series, 2019)
The cultivation of rose flowers is one of the most important economic crops, and has recently been introduced to Syrian agriculture as one of the most important or complementary crops, especially in the coastal strip, as one of the hoped-for areas for the spread of this agriculture. The study focused on the economic advantages and the material returns from the production of Jourish roses in the Syrian coast through the study of production costs and indicators of economic efficiency based on data and data collected from the sample of 40 farmers, Market prices prevailing 2018, has been pursued in this research to achieve the following objectives: - Studying the reality of the production of ornamental plants and cut flowers in Syria in general, and the Syrian coast in particular. - Calculation of the production costs of the Jour Lord in the Syrian coast, and the calculation of some economic indicators. As a result of the study, the following results were obtained: The average annual net profit realized from the plastic house planted with Al-Joury Roses was 1336922 SP /year. Profitability ratio in relation to invested capital was 35.64%, and compared to production costs 81.2%. The Lord's Capital Recovery Time Index was 2.8 years, and the economic efficiency index was 1.81 تُعدّ زراعة أزهار الورد الجوري من الزراعات الاقتصادية الهامة، وقد أٌدخِلَت إلى الزراعة السورية حديثاً كإحدى أهم الزراعات الرديفة أو المكملة، وخاصةً في الشريط الساحلي، باعتباره أحد المناطق الواعدة لانتشار هذه الزراعة. وقد تم التركيز في هذا البحث على المزايا الاقتصادية، والعوائد المادية الناتجة عن زراعة الورد الجوري في الساحل السوري، من خلال دراسة التكاليف الانتاجية، ومؤشرات الكفاءة الاقتصادية، بالاستناد إلى بيانات ومعطيات تم جمعها من عينة البحث والبالغة 40 مزارعاً، معتمدين في تحديد كلفة المواد والأجور أسعار السوق السائدة عام 2018، وقد تم السعي في هذا البحث لتحقيق الأهداف الآتية: - دراسة واقع إنتاج نباتات الزينة وأزهار القطف في سورية بشكل عام, والساحل السوري بشكل خاص. - حساب التكاليف الإنتاجية للورد الجوري في الساحل السوري، وحساب بعض المؤشرات الاقتصادية. وبنتيجة الدراسة تم التوصل إلى النتائج الآتية: بلغ متوسط صافي الربح السنوي المحقق من البيت البلاستيكي المزروع بالورد الجوري 1336922 ل.س/سنة. بلغ معامل الربحية بالقياس إلى رأس المال المستثمر 35.64%، وبالقياس إلى التكاليف الإنتاجية 81.2%. بلغ مؤشر زمن استرداد رأس المال للورد الجوري 2.8 سنة، ومؤشر الكفاءة الاقتصادية 1.81.